1984
DOI: 10.1177/014107688407700708
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Biopsies: Inaccuracy of Histological Grading in Carcinoma of the Rectum

Abstract: Summary: In a consecutive series of 70 patients with carcinoma of the rectum, 42 had operable tumours and in these the histology of the initial biopsy was compared with that of the excised specimen. In 9 of the 42 patients the histological grading of the original biopsy was different from that of the final specimen; in 3 the carcinoma was missed despite repeated preoperative biopsies; and in 5, errors were -made in the diagnosis of carcinoma in polyps. In 5 of 7 cases of poorly differentiated carcinoma the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…For example, either total rejection or total sorption would give Bi = 0 (8) Partial rejection or partial sorption would give the intermediate result 0 < Bi < C8/V0 (9) Desorption into the filtrate of previously sorbed atrazine would make the slope too large. That is Bi > C8/V0 (10) If there are no bias errors caused by membrane effects, then measured values of the slope and intercept will provide estimates of random experimental errors, independently of those that may arise during experiments with fulvic acid.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, either total rejection or total sorption would give Bi = 0 (8) Partial rejection or partial sorption would give the intermediate result 0 < Bi < C8/V0 (9) Desorption into the filtrate of previously sorbed atrazine would make the slope too large. That is Bi > C8/V0 (10) If there are no bias errors caused by membrane effects, then measured values of the slope and intercept will provide estimates of random experimental errors, independently of those that may arise during experiments with fulvic acid.…”
Section: Theorymentioning
confidence: 99%
“…Almost concurrently, Haniff et al have applied the batch dilution curve method to an investigation of the solution phase complexing of atrazine by fulvic acid (6). The work of several authors has made it clear that the risk of membrane interferences must be heeded (7)(8)(9)(10). These requirements suggest the objectives of this work.…”
mentioning
confidence: 99%
“…Grice and Hayes (2) and Grice et al (3) have described calculation techniques for the continuous flow methods, which employ areas under curves in plots of concentration vs. filtrate volume. The integral equations presented by Smedley (4) for the continuous flow methods have used the Freundlich isotherm for describing surface sorption equilibria. Buffle et al (5) and Staub et al (6) have reported the application of a batch dilution curve method to Zn(II) complexing in fulvic acid solutions.…”
mentioning
confidence: 99%
“…Local recurrence usually means an incurable disease. Attempts to perform extended resection of local recurrences are associated with high morbidity and mortality (65,85). Radiotherapy may have a good palliative effect and results in 5-year survival in a few cases (11).…”
Section: Local Recurrencementioning
confidence: 99%